Mechanical, dynamic-mechanical, and thermal properties of soy protein-based thermoplastics with potential biomedical applications - Vaz, Cláudia M. (2002)
In this study the tensile and the dynamic-mechanical behavior of injection-molded samples of various soy protein thermoplastic compounds were evaluated as a function of the amount of glycerol, type and amount of ceramic reinforcement, and eventual incorporation of coupling agents. The incorporation of glycerol into a soy-based matrix resulted in its plasticization, as confirmed by the drop in stiffness (storage and elastic modulus) above 20Â°C and a decrease in the protein glass transition temperature. Differential scanning calorimetric thermograms proved the occurrence of conformational changes in the soy protein during processing. Furthermore, the developed soy protein-based thermoplastics showed a thermal stability up to 100Â°C, as confirmed by thermogravimetric analysis. The reinforcement of the soy protein matrix with a ceramic filler (tricalcium phosphate) was shown to be effective for amounts above 10% w/w. The introduction of an amino-coupling agent led to a plasticizing effect, detected in the mechanical and dynamic-mechanical properties of the resulting materials. The results also show a good qualitative agreement between the properties obtained from quasi-static and dynamic experiments. The materials present a range of properties that might allow for their use eventually in a range of biomedical applications.